AGTR1 polymorphism is associated with elite endurance athletes: A functional study - Yang, X.; Hu, Y.; Li, Y.; Mei, T.; Gong, L. (Exercise Biochemistry Review, 2018)
Objective To explore the association between the polymorphism of angiotensin II receptor type 1 gene(AGTR1) and elite endurance athlete performance and the mechanism of how the polymorphism works.